Public administration - Sharma, Niranjan; Sharma, Gayathri (New Delhi : Vikas, 2012)
In Indian context; papers presented at a seminar held at Indian Institute of Public Administration, New Delhi, 1992.
Includes bibliographical references and index.
Keywords: Public administration -- India; India -- Politics and government -- 1947-